Implementasi Model Flippe Classroom Pada Mata Pelajaran IPS Di MTS Asy-Syakur Nglingi - M. Miftakhul Huda; Taufiq Hidayat; A. Kholiqul Amin (CV. ITTC INDONESIA, 2023)
Abstract This study aims to describe the implementation plan and the results of learning evaluation using the flipped classroom method. This research is a qualitative research using a qualitative descriptive approach. Data collection techniques in this study are using data reduction technique analysis, data presentation, and drawing conclusions. The population in this study was class VIII MTs Asy-Syakur Nglingi. The results of this study show that the evaluation results of the flipped classroom learning model obtained that of the five questions presented in the research results, namely 48,2% of students strongly agreed (SS) 38,2% of students agreed (S) and 13,6% of students doubted -doubt (R), so that the evaluation results show that the learning model with the flipped classroom method on integrated social studies subjects runs smoothly without any obstacles or obstacles. Keywords: implementation, learning model, flipped classroom